2023
DOI: 10.3389/fmolb.2023.1211621
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of gallate esters by a pH-stable tannase of mangrove-derived yeast Debaryomyces hansenii

Abstract: Introduction: Tannase is a crucial enzyme that finds wide applications in the pharmaceutical industry, feed processing, and beverage manufacturing. Although extensive studies have been conducted on tannases from fungi and bacteria, reports on tannases exhibiting favorable pH stability are relatively limited.Methods: In this study, a tannin-degrading strain Debaryomyces hansenii was screened to induce tannase production, and the corresponding tannase coding gene TANF was successfully cloned and expressed in Yar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…In this context, the ability of yeast strains isolated from Laphet-so were able to resist content at a tannic acid concentration of 50 g/L. Our findings align with the results of studies conducted by Kanpiengjai et al [7], Kanpiengjai et al [45], Pan et al [46], Song et al [47] and Zhang et al [48], where yeast strains exhibited varying degrees of tannin tolerance from different environmental sources. The observed tannin tolerance of these yeast strains aligns with previous research by Kanpiengjai et al [7], who studied yeast isolates associated with Miang (fermented tea leaves) from north Thailand.…”
Section: Evaluation Of Tannin-tolerant Abilitysupporting
confidence: 90%
See 1 more Smart Citation
“…In this context, the ability of yeast strains isolated from Laphet-so were able to resist content at a tannic acid concentration of 50 g/L. Our findings align with the results of studies conducted by Kanpiengjai et al [7], Kanpiengjai et al [45], Pan et al [46], Song et al [47] and Zhang et al [48], where yeast strains exhibited varying degrees of tannin tolerance from different environmental sources. The observed tannin tolerance of these yeast strains aligns with previous research by Kanpiengjai et al [7], who studied yeast isolates associated with Miang (fermented tea leaves) from north Thailand.…”
Section: Evaluation Of Tannin-tolerant Abilitysupporting
confidence: 90%
“…Furthermore, Pan et al [46] reported that the yeast Rhodosporidium diobovatum isolated from mangroves is capable of growing in the presence of tannic acid concentrations as high as 25 g/L. Moreover, Song et al [47] isolated 13 tannin-tolerant yeast strains from mangrove environments that thrived at a tannic acid concentration of 15 g/L, while Zhang et al [48] obtained the yeast Aureobasidium melanogenum from a red wine starter culture, which demonstrated the ability to tolerate a tannic acid concentration of 20 g/L. The observed strong tannin tolerance exhibited by our yeast isolates has significant industrial potential, particularly in the sectors involved with high tannin content substrates.…”
Section: Evaluation Of Tannin-tolerant Abilitymentioning
confidence: 99%